THE EFFECT OF ROA, LEVERAGE, AND GROWTH ON PROFIT QUALITY (CASE STUDY OF PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE) PERIOD 2020-2022 - Supriadi Siagian (Journal of Financial Management & Accounting, 2024)
This study aims to test ROA, Leverage , and Growth against Earnings Quality (case study on property and real estate companies listed on the Indonesia Stock Exchange for the period 2020-2022) . The population in this study is 1 3 property and real estate companies listed on the Indonesia Stock Exchange . This study used purposive sampling and obtained sample of 3 companies. The sample collection technique used purposive sampling method, namely taking research samples by paying attention to certain criteria based on research objectives. Data analysis using multiple linear regression with the help of SPSS software. The results of the determination coefficient test show that the Adjusted R2 value obtained is 0.834. The magnitude of the determination coefficient (R Square) is 0.870 or equal to 87%. This figure means that the variables ROA, Leverage , and Growth simultaneously have an effect on Profit Quality listed on the IDX in 2020-2022. Keywords: ROA, Leverage, Growth, Earnings Quality